Hematopoietic stem cell‐independent hematopoiesis: emergence of erythroid, megakaryocyte, and myeloid potential in the mammalian embryo. Issue 22 (27th October 2016) - Palis, James
Abstract : Steady‐state production of all circulating blood cells in the adult ultimately depends on hematopoietic stem cells (HSCs), which first arise in small numbers beginning at embryonic day (E) 10.5 in large arterial vessels of the murine embryo. However, blood cell synthesis first begins in the yolk sac beginning at E7.25 and consists of two waves of hematopoietic progenitors. The first wave consists of primitive erythroid, megakaryocyte, and macrophage progenitors that rapidly give rise to maturing blood cells of all three lineages. This 'primitive' wave of progenitors is followed by a partially overlapping wave of 'erythro‐myeloid progenitors', which contain definitive erythroid, megakaryocyte, macrophage, neutrophil, and mast cell progenitors that seed the fetal liver and jump‐start hematopoiesis before the engraftment and expansion of HSCs. These two waves of progenitors that arise in the yolk sac are necessary and even sufficient to sustain the survival of the mouse embryo until birth in the absence of HSCs. They provide key signals to support HSC emergence. Finally, HSC‐independent hematopoiesis also provides long‐lived tissue‐resident macrophage populations that function in multiple adult organs. Abstract :